2017
DOI: 10.1097/qai.0000000000001337
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of an Intervention to Maintain Suppression of HIV Viremia After Prison Release: The imPACT Trial

Abstract: Background HIV-infected individuals transitioning from incarceration to the community are at risk for loss of viral suppression. We compared the effects of imPACT, a multi-dimensional intervention to promote care engagement after release, to standard care on sustaining viral suppression after community re-entry. Methods This trial randomized 405 HIV-infected inmates being released from prisons in Texas and North Carolina with HIV-1 RNA levels <400 copies/mL to imPACT versus standard care. The imPACT arm rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 47 publications
5
38
1
Order By: Relevance
“…Although the imPACT intervention (of which mobile phone distribution and texted ART reminders comprised only one component) was not successful at maintaining virologic suppression in those released from prison, it did significantly improve attendance at an outpatient clinic appointment. 34 These results highlight the likely role and potential challenge of multiple contextual factors that are known to disrupt virologic suppression after incarceration, including environments with high rates of substance use, poverty, homelessness, discrimination, lack of employment, and lack of health insurance. 3538 …”
Section: Resultsmentioning
confidence: 83%
“…Although the imPACT intervention (of which mobile phone distribution and texted ART reminders comprised only one component) was not successful at maintaining virologic suppression in those released from prison, it did significantly improve attendance at an outpatient clinic appointment. 34 These results highlight the likely role and potential challenge of multiple contextual factors that are known to disrupt virologic suppression after incarceration, including environments with high rates of substance use, poverty, homelessness, discrimination, lack of employment, and lack of health insurance. 3538 …”
Section: Resultsmentioning
confidence: 83%
“…Compared to some of these prior studies, our observed self-reported linkage to care was higher. Specifically, the proportion of ex-inmates linking to care in studies from the United States ranges from 28 to 95%; a median of 36% was calculated in a metaanalysis [10][11][12][13][14][15][21][22][23][24][25][26]. There are several possible reasons for the potentially higher linkage to care that we observed.…”
Section: Discussionmentioning
confidence: 94%
“…We excluded from the primary outcome analysis participants who were known to have been re-incarcerated (consistent with prior analyses [15]), known to have died, or withdrew consent. Descriptive statistics were used to characterize the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent publication of Wohl et al describes a randomized controlled trial of the imPACT intervention, which had the laudable aim of preventing loss of HIV viral suppression in persons leaving prison by facilitating care access after release 1 . The objectives of the imPACT intervention are important, as engagement of vulnerable persons in care will be key to lowering community viral load.…”
Section: To the Editorsmentioning
confidence: 99%